2000
DOI: 10.2514/2.2565
|View full text |Cite
|
Sign up to set email alerts
|

Transonic-Aerodynamic-Influence-Coefficient Approach for Aeroelastic and MDO Applications

Abstract: A developed transonic-aerodynamic-in uence-coef cient (TAIC) method is proposed as an ef cient tool for applications to utter, aeroservoelasticity, and multidisciplinary design/analysis optimization. Several plausible procedures for AIC generation are described. The modal-based AIC procedure is formally established as a general AIC scheme applicable to all classes of computational uid dynamics (CFD) methods. The present TAIC method integrates the previous transonic equivalent strip (TES) method with the modal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…The results presented by Chen et al [27], as shown in Fig. 9, indicate that the transonic dip phenomenon is well characterized in the solution with the ZTAIC method [29], and the computed flutter speed also presents good agreement with the experimental data.…”
Section: B Agard 4456 Wing Aeroelastic Stability Analysissupporting
confidence: 70%
See 2 more Smart Citations
“…The results presented by Chen et al [27], as shown in Fig. 9, indicate that the transonic dip phenomenon is well characterized in the solution with the ZTAIC method [29], and the computed flutter speed also presents good agreement with the experimental data.…”
Section: B Agard 4456 Wing Aeroelastic Stability Analysissupporting
confidence: 70%
“…Table 2 presents a comparison between the transonic flutter computation based on the correction using steady and unsteady nonlinear pressures and experimental results [6]. Table 3 includes comparisons with some well-known aeroelastic analysis codes [27][28][29] with unsteady downwash correction procedure results.…”
Section: B Agard 4456 Wing Aeroelastic Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…]} (7) where U d is the control surface displacement and the last exponential term is the downwash due to a sinusoidal gust eld. The AIC matrix ordinarily relates the downwash to the aerodynamic forces on lifting surfaces.…”
Section: Uaic: Zaero Modulementioning
confidence: 99%
“…Several investigators (ref. [54][55][56][57] have calculated specific cases, but the complete trend has not been demonstrated, possibly because it is a very large computational task. It has been found that the modal data must be calculated for the wings using plate elements.…”
Section: Rectangular Wings Of Varying Thicknessmentioning
confidence: 99%